Pelatihan Daur Ulang Kantong Plastik dalam Mendukung Zero Waste School Pada Siswa MA Darul Muhsinin Desa Embung Kandong - Putra, Agus Muliadi; Widiyanti, Baiq Liana Widiyanti; Hartini, Husnayati Hartini (Universitas Hamzanwadi, 2024)
According to Law Number 18 of 2008 article 1 concerning waste, it is stated that waste is the residue of daily human activities and / or natural processes in the form of solid or semi-solid in the form of organic or inorganic substances that can be decomposed or cannot be decomposed which are considered no longer useful and disposed of in the environment. Based on its type, waste can be divided into organic and inorganic waste. Plastic waste is one of the inorganic waste that is very difficult to decompose in the environment and is very dangerous for the life of living things on this earth, including humans. Some global studies such as Jambeck et al (2015) state that plastic waste generation in Indonesia amounted to 3.2 million tons in 2010, about 1.29 million tons into marine waters. Even in another study stated that plastic waste generation of 5.4 million tons per year is equivalent to 14% of total waste while recycling plastic waste is only about 5% of total waste. In order to provide knowledge and experience to the younger generation, especially students, the Environmental Engineering Study Program of Hamzanwadi University organizes plastic waste recycling training in support of the zero waste school movement as a concrete action to help manage inorganic waste into new items that have benefits again. In addition, it also helps break the supply chain of plastic waste going to the landfill or being dumped around the school and residential environment.Keyword: Recycling, Plastic, Zero Waste